Building an Efficient Component for OCL Evaluation - Clavel, Manuel; Marina, Egea; Miguel Angel, Garcia de Dios (Electronic Communications of the EASST, 2008)
In this paper we report on our experience developing the Eye OCL Software (EOS) evaluator, a Java component for efficient OCL evaluation. We first motivate the need for an efficient implementation of OCL in order to cope with novel usages of the language. We then discuss some aspects that, based on our experience, should be taken into account when building an OCL evaluator for medium-large scenarios. Finally, we explore various approaches for evaluating OCL expressions on really large scenarios.